A Critical Review of the Impact of Inadequate Legislative Frameworks on National Security in Nigeria - Tabiowo, Ezrel (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
Inadequate legislative frameworks in Nigeria have exacerbated national security vulnerabilities, allowing threats like terrorism and insurgency to proliferate unchecked. Recent enactments, including the Terrorism Prevention and Prohibition Act 2022 (Federal Republic of Nigeria, 2022) and the Cybercrimes (Prevention, Prohibition etc.) (Amendment) Act 2024 (Federal Republic of Nigeria, 2024), reveal critical gaps in addressing evolving dangers from groups such as Boko Haram, its splinter factions ISWAP and JAS, the emerging Lakurawa network in northwestern and northeastern states, and the militant Mahmuda group in north-central regions like Kwara and Niger states. These deficiencies manifest in poorly enforced provisions on counter-terrorism, cyber defenses, border control, and internal stability, leading to heightened violence, cross-border incursions, and digital vulnerabilities. By critically analyzing the interplay between legislative shortcomings and security challenges, this review highlights how outdated mechanisms fail to adapt to dynamic threats, resulting in civilian casualties, economic disruptions, and weakened state authority. Urgent reforms are essential to bolster Nigeria's legal infrastructure for enhanced security outcomes.